Introduction to international relations - Jackson, Robert (Oxford University Press, 2010)
Fully revised and updated to cover contemporary debates in international relations, the new edition of this successful textbook will provide an ideal introduction to the theories in world politics. The strengths and weaknesses of each theory are critically examined and their main points of contention are thoroughly discussed.